THE EFFECT OF WORK SATISFACTION AND WORK STRESS ON EMPLOYEES’ TURNOVER INTENTION IN PT. TELKOM INDONESIA YOGYAKARTA - Muttaqiyathun, Ani; Rosita, Dita Ayu (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2020)
This study aims to determine the effect of job satisfaction and work stress on turnover intention. The population in this study were 104 employees who worked in the company named PT. Telkom Indonesia Yogyakarta. The results are based on saturated sampling techniques obtained 92 samples as respondents. The type of data used is primary data obtained from questionnaires answered directly by respondents who in this study employees of PT. Telkom Indonesia Yogyakarta Based on the results of multiple linear regression analysis with a significance level of 5%, it can be concluded that job satisfaction has a significant negative effect on employee turnover intention and work stress have a significant positive effect on employee turnover intention of PT. Telkom Indonesia Yogyakarta. Job satisfaction and work stress simultaneously influence turnover intention of PT. Telkom Indonesia Yogyakarta.